East and Southern Africa Office (ESAO) - International Food Policy Research Institute (2012)
IFPRI's Eastern and Southern Africa Office (ESAO), based in Addis Ababa, Ethiopia, works to strengthen IFPRI's support to Africa’s programs and development actions in the eastern and southern Africa region.